Carbohydrate gel ingestion immediately before prolonged exercise causes sustained higher glucose concentrations and lower fatigue - Kohara, A.; Morishima, T.; Uchida, H.; Ito, T.; Goto, K. (International Journal of Sport & Health Science, 2014)
The present study determined the effects of the timing of carbohydrate gel ingestion before exercise on metabolic responses and exercise performance during prolonged exercise. Methods: Seven male triathletes completed 4 different trials in a randomized order. Subjects ingested placebo immediately before the exercise (P0), or carbohydrate gel (180 kcal) immediately before exercise (C0), 45 min before exercise (C45) or 120 min before exercise (C120). Time-course changes in metabolic, hormone and subjective fatigue during 80 min of exercise (80-60% of maximal oxygen uptake) were compared among 4 trials. A 40 s maximal pedaling test was conducted immediately after 80 min of exercise. Results: Serum insulin concentrations immediately before exercise were significantly higher in the C45 trial than in the other trials (P<0.05). Blood glucose concentrations were significantly lower in the C45 trial than in the P0 and the C0 trials during the initial part of the exercise (P<0.05). During exercise, the C0 trial showed highest glucose concentration (P<0.05 vs. the other trials). The rating of perceived exertion (RPE) at 40-80 min during the exercise was significantly lower in the C0 and C120 trials than in the P0 trial (P<0.05), with no significant difference between the P0 and C45 trials. Power output during 40 s of maximal pedaling was not significantly different among the trials. Conclusions: Carbohydrate ingestion immediately before prolonged exercise resulted in higher glucose concentrations and lower subjective fatigue, especially during the last 40 min of the exercise period. However, peak and average power output during 40 s maximal pedaling immediately after the 80 min of exercise did not differ significantly among the trials.